THE RELATIONSHIP BETWEEN LEVERAGE, DIVIDEND, OWNERSHIP CONCENTRATION AND FIRM VALUE IN THE CONTEXT OF GROWTH OPPORTUNITIES (Third Sector Social Economic Review, 2022)
This study investigates whether the effect of leverage, dividends, ownership concentration on firm value differs among the firms with high and low growth opportunities. A number of firms that are listed on Borsa Istanbul Stock Exchange 100 Indices over the 2010-2020 period are analyzed using panel data analysis. The overall results show that leverage and dividends positively impact firm value, and the results are found to be significant in the group of firms with low growth opportunities. The findings are in parallel with the agency theory of overinvestment and support the disciplining role of debt and dividends in management activities. However, the study can not reach any findings related overinvestment view. The ownership concentration and firm value have a nonlinear relationship in both groups, but the direction of the relationship differs among them.
Keywords: Leverage; dividends; ownership concentration; firm value; growth opportunities